2019
DOI: 10.1172/jci123878
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CaV1.2 channels require β subunits for β-adrenergic–mediated modulation but not trafficking

Abstract: Statistics. Results are mean ± SEM. For multiple group comparisons, 1-way ANOVA followed by multiple comparison testing was performed. For comparisons between 2 groups, an unpaired Student's t test was used. Statistical analyses were performed using Prism 6 (Graphpad Software). Differences were considered statistically significant at P values less than 0.05. Data availability. The data and study materials will be made available to other researchers for purposes of reproducing the results or replicating the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 69 publications
(69 reference statements)
5
61
0
Order By: Relevance
“…When the current manuscript was under consideration, an interesting study was published reporting that AID mutant Ca V 1.2 channels, unable to bind Ca V β subunits, are insensitive to βAR stimulation with ISO or the adenylyl cyclase activator forskolin. (Yang et al ., ). The results of the present study showing dynamic augmentation of Ca V 1.2 and Ca V β 2a sarcolemmal expression upon stimulation with ISO (Figs and ) have relevance to this work, and shed more light on the importance of the Ca V β subunit in adrenergic regulation of Ca V 1.2.…”
Section: Discussionmentioning
confidence: 97%
“…When the current manuscript was under consideration, an interesting study was published reporting that AID mutant Ca V 1.2 channels, unable to bind Ca V β subunits, are insensitive to βAR stimulation with ISO or the adenylyl cyclase activator forskolin. (Yang et al ., ). The results of the present study showing dynamic augmentation of Ca V 1.2 and Ca V β 2a sarcolemmal expression upon stimulation with ISO (Figs and ) have relevance to this work, and shed more light on the importance of the Ca V β subunit in adrenergic regulation of Ca V 1.2.…”
Section: Discussionmentioning
confidence: 97%
“…61 Instead, we found that β-subunit binding to the Ca V 1.2 α 1C subunit, but not PKA phosphorylation of β, is absolutely essential for the augmentation of Ca 2+ current and cardiac contractile response to β-adrenergic−related PKA stimulation. 13 These findings identify the key regulatory mechanisms impacting β-adrenergic regulation of Ca 2+ influx and contractility in the heart. Ca V 1.2 is also a major target of CaMKII, and the resulting Ca 2+ -dependent facilitation of Ca V 1.2 current, observed as a positive "staircase" of Ca 2+ current in which current amplitude increases and inactivation slows over a series of repetitive pulses, is a powerful feed-forward effect on Ca 2+ signaling in the heart.…”
Section: Posttranslational Regulation Of Calcium Channelsmentioning
confidence: 85%
“…With this new model, we definitively demonstrate in vivo that the β subunit binding to α 1C is not required for trafficking and that the basal function of β-less Ca +2 channels is only minimally altered. 13 The α 2 δ subunit is a 175-kDa single transmembrane protein encoded by four genes (Cacna2d1, Cacna2d2, Cacna2d3, and Cacna2d4) with multiple splice variants. Although the messenger RNAs of α 2 δ 1 through 3 14 have been identified in human myocardium, only α 2 δ-1 is known to bind with Ca V 1.2 (Figure 1).…”
Section: Structure and Cellular Electrophysiological Functionmentioning
confidence: 99%
“…Further, a transgenic mouse expressing a dihydropyridine‐resistant α 1C mutant that does not bind Ca V β displayed ample DHP‐resistant Ca V 1.2 current, indicating a robust Ca V β‐independent trafficking to the sarcolemma (Yang et al . 2019). It remains to be determined whether and to what extent Ca V β‐independent trafficking happens in other cell types and other Ca V 1/Ca V 2 isoforms at different developmental stages.…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%